2016
DOI: 10.1080/02640414.2016.1206662
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lower limb work-energy patterns in world-class race walkers

Abstract: The aim of this study was to analyse lower limb work patterns in world-class race walkers. Seventeen male and female athletes race walked at competitive pace.Ground reaction forces (1000 Hz) and high-speed videos (100 Hz) were recorded and normalised joint moments, work and power, stride length, stride frequency and speed estimated. The hip flexors and extensors were the main generators of energy (24.5 J (± 6.9) and 40.3 J (± 8.3) respectively), with the ankle plantarflexors (16.3 J (± 4.3)) contributing to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 30 publications
2
27
1
Order By: Relevance
“…The aims of this study were first to analyze racewalking judges' accuracy in assessing technique and, second, to measure flight times across a range of speeds to establish when athletes were likely to lose visible contact. The study confirmed that, as occurs in elite-standard competition, each athlete had some flight time, replicating what has been shown in biomechanical research in competition (Hanley et al, 2014) and in laboratory testing (Hanley and Bissas, 2017). One key finding was that loss of contact was detected at similar rates for all groups, regardless of judge qualification status.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The aims of this study were first to analyze racewalking judges' accuracy in assessing technique and, second, to measure flight times across a range of speeds to establish when athletes were likely to lose visible contact. The study confirmed that, as occurs in elite-standard competition, each athlete had some flight time, replicating what has been shown in biomechanical research in competition (Hanley et al, 2014) and in laboratory testing (Hanley and Bissas, 2017). One key finding was that loss of contact was detected at similar rates for all groups, regardless of judge qualification status.…”
Section: Discussionsupporting
confidence: 84%
“…The force data were smoothed using a recursive second-order, low-pass Butterworth filter (zero phase-lag) at 50 Hz (Hanley and Bissas, 2017). The mean and standard deviation (SD) of the noise occurring during the final 50 ms before ground contact (visual inspection) were calculated, and first contact was considered to begin when the vertical force magnitude was greater than the mean plus 3SD of the noise (Addison and Lieberman, 2015;Hanley and Tucker, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, older electromyography studies assessed race walking before the implementation of modern race walking rules in 1995 8 and more recent studies have analysed muscle moments, power and work through inverse dynamics [9][10][11] . These estimations established the role of particular muscle group contribution to the race walking movement, suggesting the importance of smaller deceleration phases during braking in early stance and subsequent smaller acceleration phases during late stance 12 . Assessing joint kinetics in elite men and women race walkers have provided novel insight of the role of specific lower limb muscles 9 .…”
Section: Introductionmentioning
confidence: 72%
“…9 The greater activation of gluteus maximus might reduce metabolic cost by optimizing neuromuscular control to assist efficient energy transfer (muscle tuning) 19 and joint movement (hip extension and stabilisation) 17 . Understanding these specific neuromuscular profiles in relation to race walking economy may assist coaches to consider the importance of training motor control pathways when working with their athletes 12 . By training these metabolic demands maybe be decreased by a reduction in co-activation through co-ordinate and selective activation profiles of antagonist-agonist muscles.…”
Section: Terminal Swing and Initial Ground Contactmentioning
confidence: 99%